(untitled) (Comprehensive Journal of Science, 2026)
In conclusion, this research, which addressed the topic of "Seclusion: Its Concept, Types, Effects, and Interpretation from an Islamic and Psychological Perspective," reached a number of important findings. Seclusion is a complex concept that cannot be judged as absolutely positive or negative. Its impact on the psyche is determined by three fundamental factors: the individual’s intention, the duration of the seclusion, and the accompanying activity. Positive seclusion, which is a conscious choice, limited in duration, and accompanied by beneficial activities such as worship, meditation, or rest, has significant positive effects on the psyche. Among the most important of these effects are reducing stress and anxiety, increasing focus and creativity, enhancing self-awareness, improving mood, and strengthening the relationship with God. Negative seclusion, which is an escape from people or problems, or is accompanied by phone addiction, has serious negative effects on mental health. Among the most important of these effects are increased depression and social anxiety, feelings of loneliness and emptiness, weakened social skills, amplified negative thoughts and self-criticism, and sleep disturbances. Both the psychological perspective (Maslow, Altman, Jung) and the Islamic perspective emphasize that seclusion is a neutral tool; it is healthy and constructive when it serves as a means for growth and worship. Balance, which is pathological and harmful if it is a means of escaping and disconnecting from society.